ANALISIS ASUHAN KEPERAWATAN PADA PASIEN HARGA DIRI RENDAH KRONIS DENGAN INTERVENSI AFIRMASI POSITIF: ANALYSIS OF NURSING CARE IN CHRONIC LOW SELF-ESTEEM PATIENTS WITH POSITIVE AFFIRMATION INTERVENTIONS - Hasanah, Nurul; Piola, Wiwi Susanti (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2023)
Introduction: A person with chronically low self-esteem is at risk of withdrawing from social circles. So it is necessary to be given long-term therapy to control his self-confidence by intervening positive affirmations. Method: The research method uses a case study design with a nursing process approach. The subjects in this study were 3 patients in the working area of the Central City Health Center of Gorontalo City with a diagnosis of chronic low self-esteem Data collection techniques were obtained from interviews and distribution of questionnaires to see differences in signs and symptoms of chronic low self-esteem in patients before positive affirmation intervention and after positive affirmation intervention. The study was conducted during a 3-day visit. Results: The results of this study showed that after being given the Positive Affirmation technique intervention, results were obtained In Nn.HM and Mr.YD experienced a decrease in signs and symptoms of Chronic Low Self-Esteem, the patient calmed down and felt more comfortable than before. While in Ms.NM only a slight change in signs and symptoms experienced after being given this intervention, because there was no good cooperation between the patient's parents who were busy working with patients at home. Conclusion: This study shows that after the intervention of the Positive Affirmation technique is given a decrease in signs and symptoms in patients with Chronic Low Self-Esteem so that the intervention of the Positive Affirmation technique can be used as one of the interventions in patients with Chronic Low Self-Esteem.